2020
DOI: 10.1101/2020.10.21.341248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct visualization of epithelial microvilli biogenesis

Abstract: Microvilli are actin bundle supported surface protrusions that play essential roles in diverse epithelial cell functions. To develop our understanding of microvilli biogenesis, we used live imaging to directly visualize protrusion growth at early stages of epithelial differentiation. Time-lapse data revealed that an 'initiation complex' enriched in EPS8 and IRTKS appears at future sites of microvillus growth minutes before core actin bundle assembly. Elongation of a new core bundle occurs in parallel with the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Interestingly, we observed that FLN-2 displayed a shifted pattern, with an earlier apical accumulation that may suggest a specific role in microvilli establishment that needs to be analysed in detail. Thus, as in mammalian cells (Gaeta et al, 2021), C. elegans microvilli assembly might rely on an initiation complex, composed, at least, of ERM-1, ACT-5, PLST-1, FLN-2 and IFB-2, and an elongation/maturation complex, composed additionally of the actin polymerization/severing agent EPS-8, HUM-5 and MLC-5 (Fig. S5B).…”
Section: Dynamic Recruitment Of Brush Border Components During C Elegans Developmentmentioning
confidence: 85%
See 3 more Smart Citations
“…Interestingly, we observed that FLN-2 displayed a shifted pattern, with an earlier apical accumulation that may suggest a specific role in microvilli establishment that needs to be analysed in detail. Thus, as in mammalian cells (Gaeta et al, 2021), C. elegans microvilli assembly might rely on an initiation complex, composed, at least, of ERM-1, ACT-5, PLST-1, FLN-2 and IFB-2, and an elongation/maturation complex, composed additionally of the actin polymerization/severing agent EPS-8, HUM-5 and MLC-5 (Fig. S5B).…”
Section: Dynamic Recruitment Of Brush Border Components During C Elegans Developmentmentioning
confidence: 85%
“…Expression profiling in mammalian enterocytes between the proliferative crypt and the terminally differentiated villus demonstrated a marked upregulation of actin cytoskeleton-related genes, including actin, ezrin, villin and espin (Chang et al, 2008, Mariadason et al, 2005). Notably, recent data in LLC-PKI cells showed a stepwise recruitment of EPS8 and IRTKS first, and then ezrin, during microvilli outgrowth (Gaeta et al, 2021). We hypothesized that a set of brush border components may specifically be recruited at the apical pole during brush border establishment in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This kinetic difference at opposite ends creates a system that allows subunits to flux retrograde through the core bundle in a process referred to as ‘treadmilling’ (Kirschner, 1980). Indeed, recent studies with epithelial cell culture models revealed that treadmilling is crucial for microvilli assembly and motility (Gaeta et al, 2021; Meenderink et al, 2019).…”
Section: Introductionmentioning
confidence: 99%